Facing the challenges of e-learning initiatives in African universities - Gunga, Samson O.; Ricketts, Ian W. (Blackwell Publishing Ltd, 2007)
This paper explores the possibility of bringing e-learning to African universities through collaborative networks of public–private partnerships. It is envisaged that this approach will solve the dual problem of infrastructural barriers and weak ICT policies. As technology is used more in education, the teachers’ roles are increasingly integrated with those of support staff, administrators and technical staff. The needs of e-learning environments suggest the viability of multistakeholder networks to share expertise and resolve issues related to training needs. The paper concludes that collaboration networks that include e-learning sponsors, policy makers, telecommunication network service providers and educators are required to solve the problems of online education in Africa.